Forgiveness and Self Disclosure to Marital Satisfaction Working Husband and Wife - Syahri, Lia Mita; Umami, Fitria; Tursina, Siti Rahma (Indonesian Scientific Publication, 2023)
Every married individual certainly wants to achieve happiness in their marriage, marriage will not be free from conflict or problems, the findings obtained are that the high rate of divorce is because husband and wife do not get satisfaction in their marriage, this is thought to be because husband and wife are not able to forgive their partner when they make a mistake. and tend to close themselves off or not open up to their partner. The aim of this research is to describe the conditions of forgiveness, self-disclosure and marital satisfaction in working husbands and wives. The research method is literature study, based on the results of previous research to clarify the conditions of forgiveness and self-disclosure of working husbands and wives. Based on the research results, it is hoped that in the future, the research results can be useful for married couples who work, so that they can maintain their feelings or emotions, such as being able to forgive their partner's mistakes more easily and finding solutions to every problem and being able to be open in conveying what they think or feel to their partner. either husband to wife or vice versa.